The Use of Trichostatin A during Pluripotent Stem Cell Generation Does Not Affect MHC Expression Level - Sara Farahi; Sara Hosseini; Hossein Ghanbarian; Seyed Mahmoud Hashemi; Mohammad Salehi; Samaneh Hosseini (Hindawi Limited, 2022)
Pluripotent stem cells (PSCs) are considered as a potent tool for use in regenerative medicine. Highly efficient generation of PSCs through chromatin modulators such as trichostatin A (TSA) might change their MHC molecule expression profile. The efficiency of PSC generation and their immunogenicity is major obstacles for clinical use. Hence, we aim to investigate whether the use of TSA during PSC generation affects MHC expression level. Three PSC lines were generated by iPSCs, NT-ESCs, and IVF-ESCs' reprogramming methods from B6D2F1 mouse embryonic fibroblast cells. Established PSC lines were characterized by alkaline phosphatase assay (ALP) and immunocytochemistry. Their chromosome fidelity was checked by karyotyping. The expression level of pluripotent genes (oct4, nanog, sox2, klf4), HDACs (hdac1, hdac2, and hdac3), and immune-related genes (including Qa-1, Qa-2, H2kb, H2kd, H2db, H2db, CIITA, H2-IE-βb, H2-IE-βd) in iPSC and ESC lines were assessed by real-time PCR analysis. The presence of MHC molecules on the surface of pluripotent stem cells was also checked by flow cytometry technique. Significant increase of pluripotency markers, oct4, nanog, sox2, and klf4, was observed in 100 nM TSA-treated samples. 100 nM TSA induced significant upregulation of H2db in generated iPSCs. H2-IE-βd was remarkably downregulated in 50 and 100 nM TSA-treated iPSC lines. The expression level of other immune-related genes was not greatly affected by TSA in iPSC and NT-ESC lines. It is concluded that the use of short-term and low concentration of TSA during reprogramming in PSC generation procedure significantly increases PSC generation efficiency, but do not affect the MHC expression in established cell lines, which is in the benefit of cell transplantation in regenerative medicine.